2019
DOI: 10.3390/nu11030548
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Pomegranate Peel Extracts on In Vitro Human Intestinal Caco-2 Cells and Ex Vivo Porcine Colonic Tissue Explants

Abstract: The aim of this study was to determine the anti-inflammatory potential of pomegranate peel extracts (PPE) prepared from waste material of pomegranate juice production both in vitro on Caco-2 cells and ex vivo using porcine colonic tissue explants. Caco-2 cells were stimulated in vitro by TNF and colonic tissue explants were stimulated ex vivo with lipopolysaccharide (LPS). Both tissues were co-treated with PPE at 0, 1.0, 2.5, 5.0, 10 and 25 μg/mL. The secretion of CXCL8 in the supernatant of both experiments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 63 publications
5
43
0
Order By: Relevance
“…The reuse and then the valorization of the agro-industrial wastes represent an important goal for the preservation and support of a sustainable ecosystem and effective production (21). The agricultural waste recycling perfectly fits with the "zero waste concept" introduced by the circular economy strategy (22,23), and it is based on environmentally friendly processes for recovering polyphenols on both laboratory and industrial scale showing biological activities (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 94%
“…The reuse and then the valorization of the agro-industrial wastes represent an important goal for the preservation and support of a sustainable ecosystem and effective production (21). The agricultural waste recycling perfectly fits with the "zero waste concept" introduced by the circular economy strategy (22,23), and it is based on environmentally friendly processes for recovering polyphenols on both laboratory and industrial scale showing biological activities (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 94%
“…Equally, the extra protection of the food provided by the slow release of antioxidants from the package can make it possible to reduce the direct addition of chemicals to the food. Polyphenols belong to a wide category of plant derived natural compounds exhibiting many biological properties [1], including anticancer [2,3], anti-inflammatory [4,5], antimicrobial and antioxidant activity [6]. Among these compounds, gallic acid (3,4,5-trihydroxybenzoic acid, GA) and quercetin (3,3 ,4 ,5,7-pentahydroxyflavone, QC) are two potent antioxidants, due both to their redox properties and structural features (Figure 1), that impart high antioxidant activity: the three hydroxyl groups for GA [7] and the four hydroxyl groups on the A structural features (Figure 1), that impart high antioxidant activity: the three hydroxyl groups for GA [7] and the four hydroxyl groups on the A and B ring in combination with the 2,3-double bond, the 4-keto group and the 3-hydroxyl group in the C ring for QC [8].…”
Section: Introductionmentioning
confidence: 99%
“…Pomegranate extracts (pre-ether, dichloromethane, and methanol) were investigated for the anti-in lammatory effect at the dose of 100mg/kg body weight using the carrageenan-induced acute in lammatory model and compared with diclofenac as a standard drug. This study has shown 27.97% inhibition of paw oedema and other inhibitory action on prostaglandin synthesis and pro-in lammatory mediators (Mastrogiovanni et al, 2019). The pomegranate peel extract (PPE) was studied for anti-in lammatory effects and has shown the concentration-dependent activity at 0, 1.0, 2.5, 5, 10, 25 µg/ml by conquering the CXCL8 concentrations in the cell and tissue supernatants in both the in-vitro Caco-2 cell model and ex-vivo porcine colonic explant model (Lee et al, 2010).…”
Section: Effects Of Punica Granatum As An Anti-in Lammatory Agentmentioning
confidence: 52%